Guided Discovery Learning for Student Participation and Educational Well-Being in Islamic Religious Education: A Qualitative Case Study - Fuad Imali; Hasirah (WISE Pendidikan Indonesia, 2026)
This study aims to examine how guided discovery learning is implemented in Islamic Religious Education (IRE) and how it supports learner motivation, participation, and educational well-being in a junior secondary school setting. A descriptive qualitative case study was conducted in one Grade VII IRE class at State Junior Secondary School 17 of Jambi City, Indonesia. Evidence was generated through classroom observation of 32 learners, interviews with the principal, one IRE teacher, and five students, and relevant instructional documents. Iterative thematic analysis and source-technique triangulation were used to interpret the evidence. The findings show that the teacher enacted discovery learning through stimulation, problem identification, evidence seeking, collaborative processing, verification, and generalization. This guided sequence promoted curiosity, peer-assisted reasoning, independent information seeking, confidence to voice ideas, and the application of Islamic values to everyday conduct. Peer support, school encouragement, and constructive competition enabled implementation, whereas constrained lesson time, classroom-management demands, and unequal confidence limited participation. The study positions guided discovery learning as a human-centered instructional system that can broaden equitable participation and strengthen educational well-being in values-based education.